High resolution UPLC-MS/MS profiling of polyphenolics in the methanol extract of Syzygium samarangense leaves and its hepatoprotective activity in rats with CCl4-induced hepatic damage. (March 2018) - Sobeh, Mansour; Youssef, Fadia S.; Esmat, Ahmed; Petruk, Ganna; El-Khatib, Ahmed H.; Monti, Daria Maria; Ashour, Mohamed L.; Wink, Michael
Abstract: Oxidative stress plays a crucial role in the development of several liver diseases. Many natural polyphenols can attenuate oxidative stress and liver injury. In this study, a phytochemical profiling of a methanol extract from leaves of Syzygium samarangense revealed 92 compounds belonging to flavonoids, phenolic acids, condensed tannins, and ellagitannins. The S. samarangense extract exhibited a noticeable antioxidant activity with an EC50 of 5.80 μg/mL measured by DPPH scavenging capacity assay, 2632 Trolox equivalents, 10 mM Fe 2+ equivalents/mg of samples by TEAC and FRAP assays, respectively. The total phenolic content was 419 mg gallic acid equivalent GAE/g extract. In a cell-based model (HaCaT cells), the extract completely inhibited ROS production induced by UVA, and prevented GSH-depletion and p38 phosphorylation. In addition, the extract exhibited a substantial antioxidant and hepatoprotective activities in CCl4 -treated rats, with an increase in GSH (reduced glutathione) and SOD (superoxide dismutase) activities by 84.75 and 26.27%, respectively, and a decrease of 19.08, 63.05, 52.21, 37.00, 13.26, and 15.15% in MDA, ALT, AST, TB (total bilirubin), TC (total cholesterol), and TG (total glycerides), respectively. These results were confirmed by histopathological analyses. We believe that Syzygium samarangense is a good candidate for further evaluation as an antioxidant and liver protecting drug. Highlights: 92 polyphenolics were identified by UPLC-MS/MS from Syzygium samarangense leaves. Phenols included flavonol glycosides, proanthocyanidins, and ellagitannins. The extract showed potent antioxidant activity in vitro and on human keratinocytes. The extract showed a hepatoprotective potential similarly to silymarin.